CCR9 in cancer: oncogenic role and therapeutic targeting. Issue 1 (December 2016) - Tu, Zhenbo; Xiao, Ruijing; Xiong, Jie; Tembo, Kingsley; Deng, Xinzhou; Xiong, Meng; Liu, Pan; Wang, Meng; Zhang, Qiuping
Abstract Cancer is currently one of the leading causes of death worldwide and is one of the most challenging major public health problems. The main challenges faced by clinicians in the management and treatment of cancer mainly arise from difficulties in early diagnosis and the emergence of tumor chemoresistance and metastasis. The structures of chemokine receptor 9 (CCR9) and its specific ligand chemokine ligand 25 (CCL25) have been elucidated, and, interestingly, a number of studies have demonstrated that CCR9 is a potential tumor biomarker in diagnosis and therapy, as it has been found to be highly expressed in a wide range of cancers. This expression pattern suggests that CCR9 may participate in many important biological activities involved in cancer progression. Researchers have shown that CCR9 that has been activated by its specific ligand CCL25 can interact with many signaling pathways, especially those involved in tumor chemoresistance and metastasis. This review, therefore, focuses on CCR9 induction activity and summarizes what is currently known regarding its role in cancers and its potential application in tumor-targeted therapy.